Driving when distracted and sleepy: The effect of phone and passenger conversations on driving performance. (3rd June 2018) - Matthews, Raymond W.; Kontou, Thomas G.; Naweed, Anjum; Sargent, Charli; Roach, Gregory D.
ABSTRACT: This study investigates the effect of passenger and phone conversations on sleep-restricted driving. Six volunteers (50% male, mean age 24.8 ± 4.3 years) had their sleep restricted to 4 h in bed followed by a 20-min simulated drive on three separate occasions. Each drive included either a passenger conversation, a mobile phone conversation or a quiet passenger. The effect size of a phone conversation on lane deviation was large while passenger conversation was small. The main effect of conversation on lane deviation was non-significant ( F (2, 10) = 2.57, p = 0.126). Combining sleep-restricted driving with conversations warrants further investigation.